(3CSdhH QjGVjs - (3LjeS(B.(3e(B, (3gfOQShfs ((3GdQjGV(B:s (3OGQ GdeQjN(B,s, 1983)
(3fXQjGJ Sdhc GdeSJgdc, ehVhYGJ aj Sdhc GdeSJgdc, fXQjGJ GdeDSSGJ hGdTQcGJ GdJLGQjI hGdeGdjI, ehVhYGJ aj fXQjI GdeDSSI, JhGRf GdShb, GdGMJcGQ GdKfGFj hGMJcGQ GdbdI hGMJcGQ Hjf GdWQajf, JhGRf GdCShGb GdeJYOOI, ehVhYGJ aj JhGRf GdCShGb GdeJYOOI, GbJUGOjGJ GdQaGgjI, JMbjb GdCeKdjI YHQ GdRefs
(3GdedGMb U(B.451s
Keywords: (3GdEMJcGQs; (3GdEbJUGO(B-(3fXQjGJs; (3GdGbJUGO GdLRFjs; (3GdJaGVds; (3GdJcGeds; (3GdQjGVjGJ GdeGdjIs